Gestión Administrativa Y Su Incidencia En La Satisfacción Laboral De Los Empleados De La Empresa Pública Municipal De Saneamiento Ambiental De Babahoyo – Emsaba E.P. - Cabezas Barco, Hilda Leonor (2015)
The thesis raised the issue of administrative management and its impact on job satisfaction of the employees of the Municipal Public Utility Environmental Sanitation Babahoyo EMSABA - EP, was aimed to assess this impact, characterizing the current administration and determining management strategies applying management to improve the work environment, for it is to be remembered that for the efficient administration manager needs to develop administrative skills that lead to successful management, where satisfaction is a key factor for achieving the work commitments The study was a methodological process of documentary and field, with a sample population of 339 external customers, 16 employees and two managers, applying the survey and interview those involved. The results demonstrated the inefficiency of management and persisting traditional administrative features, little development of managerial skills, so if affects job satisfaction and productivity, obviously with a sense of dissatisfaction by the user. To this end proposes developing a plan to improve the administration to raise the level of job satisfaction and employee productivity Municipal Public Utility Environmental Sanitation Babahoyo EMSABA EP.